Halal Lifestyle Bagi Konsumen Muslim Generasi Z di Jawa Timur dengan Pendekatan Kajian Fenomenologi - Nurul Fazirah; Niadatus Soliha; Lailatul Qomariyah; Ersya Faraby (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to understand the meaning of halal lifestyle for Generation Z Muslim consumers in East Java through a phenomenological approach. In recent years, the concept of halal lifestyle is no longer limited to food and beverage consumption, but has expanded to include fashion, skincare, digital services, and even social media interactions. Generation Z, as digital natives, interprets halal not only as a religious rule, but also as an identity, a social trend, and a form of self-actualization. This study integrates the results of previous empirical studies that show that halal awareness, religious education, marketing strategies, and the influence of public figures play a significant role in shaping halal behavior among the younger generation. The results of the literature review indicate that Generation Z in East Java experiences complex dynamics in adopting a halal lifestyle, ranging from identity dilemmas, ethical challenges, to the influence of local culture. This phenomenological study confirms that halal lifestyle is a multidimensional phenomenon influenced by spiritual values, consumption rationality, and digital interactions. These findings are expected to provide a conceptual contribution to the study of Muslim consumer behavior and form the basis for developing a halal industry that is more adaptive to the characteristics of the younger generation..